PENERAPAN METODE GROUP INVESTIGATION DIPADU DENGAN GAME PUZZLE UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR IPA - Rahayuningsih Rahayuningsih (saintifika, 2018)
Classroom action research was conducted with the following purposes: (1) increasing learning activities of class VIIC State Junior High School 3 Jember, (2) increasing the students’ achievement in Science subject. The result of the study indicated that the implementation of GI which is combined by puzzle game could increase the activities and achievement. From the finding of the study it was suggested that teachers should use GI method which was combined by puzzle games for the teaching and learning of Science subject.